Lets celebrate - Mebrahitom, A. (Kolej Kejuruteraan, 2020)
Among the recipients of the Anugerah Perkhidmatan Cemerlang (APC) are Assoc Prof Dr Ahmed Nurye Oumer, Dr Azrul Hisyam, Ir Dr Asnul Hadi, Assoc Prof Dr Ramadhansyah Putra Jaya, Dr Khairil Azman Masri and Dr Lim Kar Sing.